2015
DOI: 10.1159/000442726
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dense Chemotherapy in Metastatic Breast Cancer: Shortening the Time Interval for a Better Therapeutic Index

Abstract: factor receptor 2 (HER2)-positive advanced breast cancer. Still, despite these advances in targeted therapies, cytotoxic chemotherapy remains a cornerstone in the treatment of advanced disease.Clearly, chemotherapy has an essential role in rapidly progressive life-threatening disease. In these situations, it is sometimes prudent to sacrifice toxicity for improved efficacy leading to rapid responses which in turn should improve the quality of life of the patient.This goal can be achieved by combining chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Emerging evidence had demonstrated that exposure time was a pivotal determinant of paclitaxel cytotoxic activity, and sufficient cytotoxicity could be exerted under relatively low blood concentration if exposure time were extended [ 13 , 24 , 25 ]. Second, dose-dense therapy delivered chemotherapy drugs weekly, which could shorten the interval time and increase the density of drug delivery [ 26 ]. Besides, the valley of paclitaxel blood concentration was higher than that of three-weekly therapy [ 27 ], and the cumulative dose of paclitaxel for dose-dense therapy was more than that of conventional three-weekly therapy (240 mg VS 175 mg) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence had demonstrated that exposure time was a pivotal determinant of paclitaxel cytotoxic activity, and sufficient cytotoxicity could be exerted under relatively low blood concentration if exposure time were extended [ 13 , 24 , 25 ]. Second, dose-dense therapy delivered chemotherapy drugs weekly, which could shorten the interval time and increase the density of drug delivery [ 26 ]. Besides, the valley of paclitaxel blood concentration was higher than that of three-weekly therapy [ 27 ], and the cumulative dose of paclitaxel for dose-dense therapy was more than that of conventional three-weekly therapy (240 mg VS 175 mg) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…FDA approved chemotherapy drugs for breast cancer include taxanes, anthracyclines, and platinum. Compared to the standard schedule of treatment (every three-weeks), combination of doxorubicin, cyclophosphamide, and paclitaxel administered every two weeks with high density has slowed cancer growth and extended survival without introducing additional adverse side effects [ 35 ].…”
Section: Breast Cancermentioning
confidence: 99%
“…This is supported by existing literature [ 6 ]. The efficacy of medication may be compromised if the administered doses, whether orally or intravenously, do not adequately reach the intended sites, as per sources [ 7 , 8 ]. Targeted therapies and immunotherapies represent a novel and auspicious approach to managing breast cancer [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%